Abd Al-Malik Ibn Marwan's Economic Reform: The Influence of Standard Currency in the Umayyad Caliphate - Bayu Sukma (Sekolah Tinggi Agama Islam Kuningan, 2026)
Backround: Abd al-Malik ibn Marwan, the Umayyad caliph who ruled from 685 to 705 CE, is recognized as a pivotal figure in the economic history of early Islamic civilization. Objective: This study examines the nature, process, and long-term consequences of his monetary reforms, with particular emphasis on the standardization of gold dinars and silver dirhams as the official currency of the Umayyad Caliphate. Method: This article employs a qualitative-historical methodology, drawing on primary classical sources and contemporary scholarly literature. Findings and Implications: These reforms addressed chronic problems of inflation, monetary fragmentation, and fiscal instability that had adversely affected trade and state administration. By establishing uniform weight standards and replacing Byzantine and Sasanid coins with distinctly Islamic currency bearing Quranic inscriptions, Abd al-Malik created a monetary system that facilitated interregional commerce, reinforced Islamic political identity, and enhanced confidence in the caliphate's financial institutions. Conclusion: The analysis demonstrates that Abd al-Malik's currency reforms constituted a foundational contribution not only to Umayyad economic governance but also to the broader trajectory of Islamic economic thought and practice.